Child Injury in Israel: Emergency Room Visits to a Children's Medical Center - Michal Hemmo-Lotem; Claudia Jinich-Aronowitz; Liri Endy-Findling; Michal Molcho; Michal Klein; Yehezkel Waisman; Yehuda L. Danon; Joav Merrick (The Scientific World Journal)
The object of this study was to provide data for policy making and prevention program planning in Israel. The study examined all visits to the Department of Emergency Medicine at the Schneider Children's Medical Center in 1996 (41,279 visits in total). Approximately 22.6% of the emergency room patients were admitted following injury. Most (97%) were unintentional injury. Approximately 42% of the patients were less than 4 years old and about 20% were 2 years old. In all age groups, the rate of boys was double. Approximately 92% were Jews. Despite this low rate of non-Jewish patients, however, they constituted 20% of later hospitalizations. The main injuries recorded were bruises and wounds from blunt objects, falls, motor vehicle–related accidents, and sport injuries. The most commonly injured body parts were the head and upper and lower limbs. In 82%, medical treatment was reported and 7% were hospitalized. In examining injuries over the year, there were no significant differences between the different months, but there were clusters of injuries around various holidays—bicycle and skateboard accidents at Rosh Hashanah, Yom Kippur, and Succoth; pedestrian accidents around Lag BaOmer; burns on Purim, Hannukkah, and Passover; and accidental poisoning around Passover. The findings gave an indication of the nature of the injured population groups. These data could be useful for prevention strategy, both on the level of physical injury as well as on the level of the times of the year, when the risk was higher. The data collected very strongly raise the urgent need for establishing a national surveillance system, which would allow tracking injury-related data with respect to young people throughout the country.